2015
DOI: 10.1093/cvr/cvv130
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Hsp60 orchestrates the survival and inflammatory responses of vascular smooth muscle cells in injured aortic vessels

Abstract: This study provides the first evidence that cytosolic Hsp60 could be a therapeutic target for preventing VSMC hyperplasia and inflammatory response in the injured vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Additionally, OSMR-β −/− ApoE −/− mice exhibited a dramatic increase in the content of collagen and SMCs, but a decrease in macrophage infiltration and lipid accumulation. It has been demonstrated that the inflammation induced by TNF-α or IL-1β can promote matrix-degrading metalloproteinase expression and promote tissue remodeling (34, 35), and TNF-α facilitates oxidative stress in SMCs and accelerates vascular SMC apoptosis (36, 37). Correspondingly, previous studies have demonstrated that advanced lesions are characterized by the apoptosis and necrosis of macrophages or other cell types, which results in the release of lipids and inflammatory mediators and the formation of the necrotic core.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, OSMR-β −/− ApoE −/− mice exhibited a dramatic increase in the content of collagen and SMCs, but a decrease in macrophage infiltration and lipid accumulation. It has been demonstrated that the inflammation induced by TNF-α or IL-1β can promote matrix-degrading metalloproteinase expression and promote tissue remodeling (34, 35), and TNF-α facilitates oxidative stress in SMCs and accelerates vascular SMC apoptosis (36, 37). Correspondingly, previous studies have demonstrated that advanced lesions are characterized by the apoptosis and necrosis of macrophages or other cell types, which results in the release of lipids and inflammatory mediators and the formation of the necrotic core.…”
Section: Discussionmentioning
confidence: 99%
“…Hsp60 activation of the IKK/NF-κB pathway for survival can be seen in vascular smooth muscle cells where it can prevent apoptosis as well as promote neointimal thickening of the damaged vessels. However, persistent activation of the pathway has been linked to various chronic inflammatory diseases such as cancer and atherosclerosis ( Choi et al, 2015 ). From the cytosol, Hsp60 can leave the inside of the cell and attach itself to the cell’s surface or enter the extracellular space through secretory vesicles ( Campanella et al, 2012 ).…”
Section: Chaperonopathies and The Role Of Mthsp60 In Diseasementioning
confidence: 99%
“…The mtHsp60 encoding gene HSPD1 is a nuclear gene that is translated in the cytosol and imported into the mitochondria due to the presence of an N-terminal mitochondrial targeting sequence that is cleaved upon translocation across the mitochondrial membrane ( Cheng et al, 1989 , 1990 ; Reading et al, 1989 ; Singh et al, 1990 ). A small fraction of Hsp60 resides in the cytosol and also at the cell surface but the function outside of the mitochondria has not been well established ( Soltys and Radhey, 1997 ; Chun et al, 2010 ; Choi et al, 2015 ; Kalderon et al, 2015 ). Chaperonins carry out protein folding cycles in an ATP-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Both TNF‐α and IL‐1β, for example, induce matrix‐degrading metalloproteinase expression and promote tissue remodeling . In addition, TNF‐α facilitates increases in oxidative stress in VSMCs and facilitates VSMC apoptosis . In contrast to these proinflammatory cytokines, IL‐10 is a potent anti‐inflammatory cytokine with the ability to deactivate macrophages .…”
Section: Discussionmentioning
confidence: 99%
“…34,35 In addition, TNF-a facilitates increases in oxidative stress in VSMCs and facilitates VSMC apoptosis. 36,37 In contrast to these proinflammatory cytokines, IL-10 is a potent anti-inflammatory cytokine with the ability to deactivate macrophages. 38 Consistent with these studies, we found that vinexin b À/À apo E À/À mice exhibited more stable lesions characterized by diminished necrotic cores and increased collagen and VSMC content.…”
Section: Discussionmentioning
confidence: 99%